The Evaluation of Antioxidant Activity and Cytotoxicity of Leaf, Orange Fruit, and Calyx Extract of Physalis alkekengi on Human Lung Cancer A549 Cell Line - Babakhani, Babak; Houshani, Mahdieh; Motallebi Tala Tapeh, Sogol; Hosseini Boldaji, Seyed Afshin; Shoja Shafiee, Maryam; Arman, Mitra; Heidari keshel, Saeed (Regeneration, Reconstruction & Restoration (Triple R), 2021)
Introduction: Lung cancer is the most common cancers, and chemotherapy treatment as one of the methods leads to the occurrence of intolerable side effect. Thus recently, natural products extracted from medicinal plants can play an important role in cancer treatment. It was aimed in this study, based on medicinal effect of the Physalis alkekengi, to determine the content and activity of some antioxidant compounds of leaves, orang fruits, and calyx of P. alkekengi and also the inhibitory effects of their crude extract on lung cancer A549 cell line. Materials and Methods: Leaf, Orange Fruit, and Calyx Extract of P. alkekengi were harvested from the region of Tonekabon city and A549 cells line was cultivated and proliferated. Then, the cells exposed to different concentrations of the leaves, fruits ,and calyx extract of P. alkekengi (31.25 to 2000 μg/ml) were incubed for 24, 48, and 72 hours. After the incubation period, the colorimetric MTT method was used to determine cytotoxicity. Also, total phenol, flavonoid, anthocyanin, and carotenoid contents were determined as well as antioxidant activity of extract using DPPH method. Results: The results showed that the highest total phenol, flavonoids, and anthocyanins were in leaves and the highest antioxidant activity and total carotenoids were seen in fruits. The results have also shown that the extracts of leaves, fruits, and calyxes brought the highest inhibition of cancer cell growth at the concentration level of 2000 μg/ml that were 88.55, 91.81, and 94.97% respectably. Conclusion: These results suggest that the leave, fruit and calyx of ethanolic extract of P. alkekengi have the most antioxidant and antimicrobial activity and cytotoxicity against A549 cell line. It seems to come with further research, and utilizes its compound in cancer treatment.